Aquatic Invertebrate Antimicrobial Peptides in the Fight Against Aquaculture Pathogens - Tomás Rodrigues; Francisco Antonio Guardiola; Daniela Almeida; Agostinho Antunes (Microorganisms)
The intensification of aquaculture has escalated disease outbreaks and overuse of antibiotics, driving the global antimicrobial resistance (AMR) crisis. Antimicrobial peptides (AMPs) provide a promising alternative due to their rapid, broad-spectrum activity, low AMR risk, and additional bioactivities, including immunomodulatory, anticancer, and antifouling properties. AMPs derived from aquatic invertebrates, particularly marine-derived, are well-suited for aquaculture, offering enhanced stability in high-salinity environments. This study compiles and analyzes data from AMP databases and over 200 scientific sources, identifying approximately 350 AMPs derived from aquatic invertebrates, mostly cationic and α-helical, across 65 protein families. While in vitro assays highlight their potential, limited in vivo studies hinder practical application. These AMPs could serve as feed additives, therapeutic agents, or in genetic engineering approaches like CRISPR/Cas9-mediated transgenesis to enhance resilience of farmed species. Despite challenges such as stability, ecological impacts, and regulatory hurdles, advancements in peptidomimetics and genetic engineering hold significant promise. Future research should emphasize refining AMP enhancement techniques, expanding their diversity and bioactivity profiles, and prioritizing comprehensive in vivo evaluations. Harnessing the potential of AMPs represents a significant step forward on the path to aquaculture sustainability, reducing antibiotic dependency, and combating AMR, ultimately safeguarding public health and ecosystem resilience.